2022
DOI: 10.1111/fcp.12764
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute ethanol and/or diazepam exposure on immediate and delayed hippocampal metabolite levels in rats anesthetized with isoflurane

Abstract: Alcohol and benzodiazepines are psychoactive substances frequently associated in voluntary drug intoxications that share common mechanisms of action, including facilitation of GABAergic transmission. This study aimed to assess the separate and combined effects of ethanol and diazepam acute exposure on hippocampal metabolite levels, as well as on delayed cognitive performance, in rats anesthetized with isoflurane. Adult male Wistar rats received one intraperitoneal injection containing either saline solution (“… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…6D6T for GABA receptor was used and its cocrystallized ligand in diazepam binding site was used to provide coordinates to the software. After successful completion of docking protocol, binding energies of the compounds were compared with diazepam (Carton et al, 2022). The results showed that binding energies of gallic acid (-20 kcal/mol), kaempferol (-16 kcal/mol) were much more negative than the diazepam (-9 kcal/mol), indicating that gallic and kaempferol have much higher binding a nities than the diazepam.…”
Section: In Silico Studymentioning
confidence: 99%
“…6D6T for GABA receptor was used and its cocrystallized ligand in diazepam binding site was used to provide coordinates to the software. After successful completion of docking protocol, binding energies of the compounds were compared with diazepam (Carton et al, 2022). The results showed that binding energies of gallic acid (-20 kcal/mol), kaempferol (-16 kcal/mol) were much more negative than the diazepam (-9 kcal/mol), indicating that gallic and kaempferol have much higher binding a nities than the diazepam.…”
Section: In Silico Studymentioning
confidence: 99%